Osmo-priming in tomato seeds down-regulates genes associated with stress response and leads to reduction in longevity - Petronilio, Ana C.P. [UNESP]; Batista, Thiago B. [UNESP]; Amaral Da Silva, Edvaldo A. [UNESP] (Cambridge University Press (CUP), 2021)
Tomato seeds subjected to osmo-priming show fast and more uniform germination. However, osmo-priming reduces seed longevity, which is a complex seed physiological attribute influenced by several mechanisms, including response to stress. Thus, to have new insights as to why osmo-primed tomato seeds show a short life span, we performed a transcript analysis during their priming. For that, we performed gene expression studies of the heat-shock protein family genes that were previously reported to be associated with the enhancement of longevity in primed tomato seeds. Physiological assays of germination, vigour and longevity tests were used to support the data. The results show that the short life span of osmo-primed tomato seeds is related to the decrease in the expression of transcripts associated with response to stress during the priming treatment. These results are important because they add information regarding which seed longevity mechanisms are impacted by the priming treatment. In parallel, it will allow the use of these genes as markers to monitor longevity in osmo-primed tomato seeds.
Keywords: conservation; primed seeds; Solanum lycopersicum; stress response